Drugs and high hospitalization rate: are they related? - I. M. Figueiredo; I. Cargaleiro; M. Nascimento (European Psychiatry, 2023)
Introduction Substance use continues to be an important problem among mental health patients either as main diagnosis or as comorbidity. Acute care visits, including emergency department visits and hospitalizations, related to substance use disorders (SUD) are increasing and can be opportunities to engage individuals to get proper treatment (Suen LW et al. J Gen Intern Med 2022; 37(10):2420–2428).